Prognostic value of serum calprotectin level in elderly diabetic patients with acute coronary syndrome undergoing percutaneous coronary intervention: A Cohort study. Issue 33 (14th August 2020) - Zhang, Wutang; Wang, Yongmei; Wang, Lizhi; Song, Lizhong; Tan, Lijuan; Xue, Xiaobo
Abstract : Abstract: Patients with acute coronary syndrome (ACS) have an increased serum level of calprotectin. The purpose of present study was to analyze the prognostic significance of serum calprotectin levels in elderly diabetic patients underwent percutaneous coronary intervention (PCI) due to ACS. A total of 273 consecutive elderly diabetic patients underwent PCI for primary ACS were enrolled. Serum calprotectin levels were measured before PCI, and baseline clinical characteristics of all patients were collected. All patients were followed up at regular interval for major adverse cardiovascular events (MACEs) during 1 year after PCI. MACEs include cardiovascular death, nonfatal myocardial infarction, and target vessel revascularization (TVR). The predicting value of serum calprotectin for MACEs was analyzed by using univariate and multivariate analysis and receiver-operating characteristic curve (ROC). At the endpoint of this study, 47 patients of all 273 patients had MACEs. According to optimal cutoff value of calprotectin for predicting MACEs by ROC analysis, all patients were stratified into a high calprotectin group and a low calprotectin group. The incidence rate of MACEs and TVR in high calprotectin group was prominently higher than that in low calprotectin group (21.9% vs 11.5%, P  = .02). In multivariable COX regression analysis adjusting for potential confounders, serum calprotectin level remains as an independent risk predictor of MACE (hazard ratio, 1.56; 95% confidence interval [CI]: 1.08–4.62; P  = .01). In diabetic patients with a comorbidity of ACS, a high serum level of calprotectin is associated to a higher MACE rate after PCI.